Entrepreneurship Study Group Education: Juvenile Delinquency Prevention Program through Entrepreneurship Formation Using Social Media in Turida Village, Mataram City - Triana Lidona Aprilani; Laili Hurriati; Mimi Cahayani; Sri Karyati (LPPM Institut Studi Islam Sunan Doe, 2024)
The specific objectives of implementing this PkM activity are: (1) Forming study groups among youth in making animation, (2) Providing input, insight, and knowledge about youth, (3) Reducing the level of juvenile delinquency which continues to increase from year to year, and (4) Equipping youth with entrepreneurial skills by using social media to reduce their free time. For the sake of the continuity of this community service activity, a method that can be digested and absorbed directly by the sons and daughters of teenagers in Turida Babakan Village, Mataram City, namely; The